Examination Questions and Answers in Basic Anatomy and Physiology 2000 Multiple Choice Questions - Caon, Martin (Springer Nature Singapore : Imprint: Springer, 2016)
This book provides two thousand multiple choice questions on human anatomy and physiology, separated into 40 categories. The answer to each question is accompanied by an explanation. Each category has an introduction to set the scene for the questions to come. However not all possible information is provided within these Introductions, so an Anatomy and Physiology textbook is an indispensable aid to understanding the answers. The questions have been used in examinations for undergraduate introductory courses and as such reflect the focus of these particular courses and are pitched at the level to challenge students that are beginning their training in anatomy and physiology. The questions and answer combinations are to be used both by teachers, to select questions for their next examinations, and by students, when studying for an upcoming test. Students enrolled in the courses for which these questions were written include nursing, midwifery, paramedic, physiotherapy, occupational therapy, nutrition & dietetics, health sciences and students taking an anatomy and physiology course as an elective.